EVALUASI PROGRAM PENINGKATAN KINERJA APARATUR SIPIL NEGARA (ASN) DINAS KESEHATAN KABUPATEN MOJOKERTO - Fefi Aryani Kuswandi; Eka Diah Kartiningrum; Bakti Tunjung Pranoto; Santy Wahyu Nuraini; Dhonna Anggreni (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2024)
The ASN professionalism index (IP) is a statistical measure that describes the quality of ASN based on the educational qualifications, competence, performance and discipline of ASN employees in carrying out their job duties. The aim of this service activity is to evaluate the Performance Improvement Program for State Civil Apparatus (ASN) within the Mojokerto District Health Service in 2023. This activity was carried out in March 2023. The activity was carried out in the stages of analyzing the situation, identifying problems, determining problem priorities, determining alternative solutions. problems, determining activity plans, implementing activities and evaluating activities. The results of the activities obtained are that the performance of the ASN Health Service has increased in 2023. The performance of the ASN Mojokerto District Health Service has changed for the better with the SUHITA Application. The majority of employees have passed the set target points. The Personnel Section of the Mojokerto District Health Service should publish the results of the performance assessment within the Mojokerto District Health Service at every meeting so that it can be a motivation for ASN.